Teriparatide mitigates oxidative stress following spinal cord injury and enhances neurological recovery via the Nrf2/HO-1 signaling pathway - Moliang, Xiong; Gangtong, Ai; Yun, Feng; Caiguang, Luo; Liang, Deng; Jia, Guo; Qiang, Xiao (Frontiers in Pharmacology, 2025)
IntroductionSpinal Cord Injury (SCI) represents a devastating form of central nervous system trauma, where oxidative stress plays a critical role in the ensuing pathology. Targeting oxidative stress presents a viable therapeutic avenue. Teriparatide, a synthetic analog of parathyroid hormone, is conventionally utilized for osteoporosis and bone defect management. Emerging evidence suggests teriparatide’s potential in modulating oxidative stress in ischemic stroke, yet its efficacy in SCI remains underexplored.Methods We investigated the neuroprotective effects of teriparatide in a rat spinal cord injury (SCI) model. Teriparatide was administered to animals post-injury, and functional recovery was assessed using the open field test and Basso-Beattie-Bresnahan (BBB) locomotor rating scale. Molecular analyses included evaluation of Nrf2 pathway activation and antioxidant protein expression via immunofluorescence, Western blot, and ELISA. Additionally, glutathione peroxidase (GSH-PX) activity and malondialdehyde (MDA) levels were measured using commercial assay kits.ResultsWe obtained two significant results: Firstly, teriparatide treatment significantly enhanced motor function recovery post-SCI. Secondly, teriparatide upregulated Nrf2 expression, which subsequently increased the production of the antioxidant proteins HO-1 and SOD2, reduced MDA levels in spinal tissues, and boosted GSH-PX activity.ConclusionOur findings demonstrate that teriparatide activates the Nrf2/HO-1 antioxidant pathway, effectively mitigating oxidative damage in SCI. This repositioning of an FDA-approved osteoporosis drug presents a clinically translatable strategy for neuroprotection.